2004
DOI: 10.1542/peds.2004-0385
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Stroke in Children With Motor Impairment: A Population-Based Study

Abstract: ABSTRACT. Objective. Risk factors for perinatal arterial stroke (PAS) are poorly understood. Most previous studies lack an appropriate control group and include only infants with symptoms in the newborn period. We set out to determine prenatal and perinatal risk factors for PAS.Methods. In a population-based, case-control study nested within the cohort of 231 582 singleton infants who were born at >36 weeks' gestation in Northern California Kaiser hospitals from 1991 to 1998, we searched electronically for chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
119
5
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(139 citation statements)
references
References 58 publications
9
119
5
6
Order By: Relevance
“…When it occurs during the perinatal period, arterial ischemic stroke is associated with considerable lifetime burden such as cerebral palsy (CP), cognitive impairment, and epilepsy. [1][2][3][4][5][6][7] Various terms have been used to describe arterial ischemic stroke during the perinatal period. Because of a lack of consistency among studies, its terms were defined in a workshop of the National Institute of Child Health and Human Development and the National Institute of Neurologic Disorders and Stroke.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When it occurs during the perinatal period, arterial ischemic stroke is associated with considerable lifetime burden such as cerebral palsy (CP), cognitive impairment, and epilepsy. [1][2][3][4][5][6][7] Various terms have been used to describe arterial ischemic stroke during the perinatal period. Because of a lack of consistency among studies, its terms were defined in a workshop of the National Institute of Child Health and Human Development and the National Institute of Neurologic Disorders and Stroke.…”
mentioning
confidence: 99%
“…Hospital-and population-based studies in North America and Europe have provided epidemiologic data suggesting that the incidence of ischemic perinatal stroke is between 5 and 43 per 100 000 live births. 2,[10][11][12][13][14][15][16][17][18] Studies have shown that about half of patients become symptomatic during the neonatal period. 14 A summary of epidemiologic studies on NAIS and PPIS is presented in Table 1.…”
mentioning
confidence: 99%
“…low apgar scores or the presence of seizures and, particularly where data is based on the presence of relatively subtle findings, it may be difficult to conclude whether these abnormalities are causal or have occurred as a consequence of an underlying cerebral abnormality. This is highlighted in the case-control study where, although there was an increased incidence of non-specific perinatal abnormalities in the affected group, there was no significant difference between cases and controls in those diagnosed with significant birth asphyxia (Wu et al, 2004). Similarly, documented no cases with evidence of severe birth asphyxia in a series of 24-term infants with stroke, however, 14/24 had abnormal perinatal findings including abnormal CTG recordings and 11/24 had meconium-stained liquor.…”
Section: Risk Factorsmentioning
confidence: 95%
“…On multivariate analysis, antenatal risk factors significantly associated with stroke were pre-eclampsia [odds ratio (OR): 3AE6; 95% confidence interval (CI): 1AE1-11AE4] and intrauterine growth retardation (IUGR) (OR: 5AE3; 95% CI: 1AE5-18AE6). Other significantly associated perinatal factors were emergency Caesarean section, 5-min apgar scores <7, and resuscitation at birth (Wu et al, 2004).…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation